MEKANISME PEMBUATAN SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN OLEH NOTARIS/PPAT - , DANAR SRI GURITNO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The author chose the title of the final project report \"Mechanisms for Imposing Power of Attorney Mortgage By Notary / PPAT, because the authors wanted to understand more about the making of the Power of Attorney Charge Mortgage and provide more information to the public about the Power of Attorney Charge Mortgage. The author chose a place in the Office of Field Work Practice Notary and PPAT Nurhadi Darussalam, SH, M. Hum is located at Jalan Affandi Gang Bougenville CT X/07 Caturtunggal, Depok, Sleman, Yogyakarta Special Region for 2 (two) months from the date or eight mingguterhitung February 25, 2013 until 26 April 2013. The purpose of this final project is to meet the course requirements for graduation from the Diploma Programme 3 Vocational School of Law, Gadjah Mada University and earned his Associate Expert for Law (A.Md). The benefits of this practice is to give the Job direct experience like interacting with JV and get a lot of lessons directly. The results of this report directing that the Power of Attorney can impose Mortgage Notary or PPAT, Power of Attorney Charge Mortgage Mortgage made because the grantor can not attend in person to sign the Mortgage Deed Granting in charge of mortgage. Imposition of Mortgage shall be registered in the Land Office, which then issued the certificates Mortgage.